Ritual Megocek Taluh Pada Upacara Pujawali Pura Maksan Banjar Pajang (Perspektif Agama Hindu) - I Made Ardika Yasa (Jurnal Penelitian Agama Hindu, 2022)
Megocek Taluh ritual that is held every celebration of Pujawali Ceremony Maksan Banjar Pajang Temple to ask for the grace of safety, success and beauty, And as a form of gratitude to the spirit of their ancestors who are puja as Ida Betara Bagus Bebotoh who is believed to be one of the Ida Betara who berstana in Pura Maksan Banjar Pajang who according to the interpreter of the temple he is none other than the embodiment of the Manik Angkeran who is the son of Rsi Sidhi Mantra, Megocek Taluh ceremony will not take place if Maksan Banjar pajang temple pujawali is not performed because the ceremony of Pujawali Pura Maksan Banjar Pajang and Megocek Taluh Ceremony is a series like two currency sidebars that cannot be separated. Megocek Taluh ceremony is carried out systematically through various ritual processions to give wisdom that gambling will not make the perpetrator rich even if packaged in any form. Megocek Taluh ceremony has a huge role and function in the context of building educational value to the participants, researchers, and visitors of Pujawali Pura Maksan Banjar Pajang ceremony because in the Megocek Taluh Ritual there is value; (1) Social Education, (2) Cultural Education, (3) psychological education because the ceremony of Megocek Taluh as a vehicle for Self-Instropeksi, (4) Cultural Education Symbol, In the ceremony Megocek Taluh there is a profound meaning, namely; (1) As an application of Panca Yadnya, (2) As an Application of Tri Hita Karana, (3) As an application of Tatwam Asi, (4) Has a socio-cultural meaning, (5) Has the meaning of Hindu religious education, (6) Has religious meaning, (7) As a form of sportsmanship.